Avaliação da eficiência de lâmpadas UV (254 nm e 185+254 nm) na degradação do Roxarsone - Elias, Anna Carolina Felippe (Universidade Federal de São Carlos, 2025)
Roxarsone (ROX) is an organoarsenic compound used as a feed additive for poultry and swine to promote growth and control intestinal parasites. Less than 10% is retained by the animals; most of it is excreted and reaches the environment through the application of manure to agricultural areas. ROX can be converted into toxic inorganic arsenic species (As3+ and As5+), posing risks to soil, water, and human health. Its use has been banned in several countries, including Brazil, since 2002. Photolysis stands out as one of the main natural mechanisms for ROX degradation in aquatic environments. The present study aimed to compare the degradation of roxarsone by photolysis using two ultraviolet radiation sources: 254 nm and 185 + 254 nm. For this purpose, aqueous ROX solutions (0.01 g L-1) were irradiated in a photoreactor, and samples were analyzed every 30 minutes over a total period of 300 minutes. Analyses were performed by UV–Vis spectrophotometry, with data treatment through concentration–time curves, percentage degradation efficiency, and first-order kinetics. The results showed that ROX underwent degradation under both radiation sources. With 254 nm, a gradual decrease in concentration was observed, evidenced in the UV–Vis spectra and confirmed by first-order kinetics. In contrast, 185 + 254 nm showed significantly superior performance, with a degradation rate approximately four times higher than that obtained with the 254 nm alone. Direct comparison between the methods demonstrated that the presence of 185 nm radiation substantially enhances ROX degradation. The degradation efficiency at the end of the experiment was 15.7% for 185 + 254 nm and 4% for 254 nm, evidencing the increased efficiency of ROX degradation in aqueous solution.
Evaluation of the efficiency of UV lamps (254 nm and 185+254 nm) in the degradation of Roxarsone
Keywords: Organoarsênico; Aditivo alimentar; Esterco; ROX; Fotólise; Organoarsenic; Food additive; Manure; Photolysis; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA; 2. Fome Zero e Agricultura Sustentável; 3. Saúde e Bem-Estar; 6. Água Potável e Saneamento; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis